Association between self-reported empathy and level of physical activity in healthy young adults - Takeru Shima; Subrina Jesmin; Hayato Nakao; Kentaro Tai; Tomonori Shimofure; Yoshihiro Arai; Keiko Kiyama; Yoko Onizawa (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Empathy, which consists of cognitive and affective empathy, is one of the vital skills in humans for creating and maintaining relationships with others, now, there are many empathy-deficient people, possibly deriving from an increase in harassment-related issues. Although there is a possibility that physical activity improves empathy, the association of physical activity with cognitive and affective empathy in healthy humans remains unclear. Thus, the present study aims to clarify the relationship between levels of physical activity and self-reported empathy. Eight hundred and ninety-three responses for two questionnaires, the short version of the International Physical Activity Questionnaire (SV-IPAQ) and Questionnaire of Cognitive and Affective Empathy (QCAE), were analyzed. Levels of physical activity in a usual week were measured based on the SV-IPAQ, and participants were divided into three groups: low, moderate and high physical activity. The scores for cognitive and affective empathy were measured based on QCAE. We found that people with a moderate or high physical activity level show significantly higher self-reported cognitive empathy compared to people with a low physical activity level. The score for self-reported affective empathy wasn't affected by physical activity level. Physical activity level in a usual week showed a significant positive correlation with self-reported cognitive empathy scores, but not with self-reported affective empathy scores. Our findings imply that an increase in physical activity contributes to better cognitive empathy in healthy young adults.